(untitled) (Research, Society and Development, 2022)
In Brazil, the concept of education has undergone changes as occurred in the social, political and technological spheres of society as a whole, causing education to receive the same transformations, as it must accompany society. Receiving a more humanized and dynamic character, education places the student at the center of the educational process as an asset in their learning, while understanding that this must be democratic and participatory, overlapping the concept of school administration with that of management. Currently, it is necessary to debate Brazilian school management, which is the object of this study, as well as pointing out some pertinent issues that directly imply its development. To this end, a descriptive, exploratory and qualitative bibliographic research was carried out. The search was carried out in a virtual environment in which scientific articles are found in databases, publications, books in pdf and printed format, with the descriptors school management, democratic management, profile and portrait. A textual analysis was carried out on the material found, seeking concepts, relationships and clarifications on results and consequences. The results and discussions were presented in three sequential titles, and the conclusions presented in the final considerations.